Banana lectin (BanLec) induces non-specific activation of basophils and mast cells in atopic subjects - Krithika, N.; Pramod, S.N.; Mahesh, P.A.; Venkatesh, Y.P. (European annals of allergy and clinical immunology, 2018)
Dietary lectins play a major role in the activation of mast cells / basophils by bridging cell surface IgE glycans to release histamine and other mediators. In the present study, the effect of mannose / glucose-specific banana lectin (BanLec) on the activation of mast cells / basophils from non-atopic and atopic subjects has been investigated. BanLec was purified from banana pulp in a yield of 7 mg/kg. Leukocytes isolated from heparinized blood of non-atopic / atopic subjects were used for quantitation of the released histamine. Approximately 28.2% of the atopics (n = 117) was positive by skin prick test (SPT) to purified BanLec (100 mg/mL concentration), and all the non-atopics (n = 20) were negative. Maximal release of histamine was seen at 2 g of BanLec. In percent histamine release, an increase of 35-40% is observed in case of atopics (n = 7) compared to non-atopics (n = 5), and the histamine release from atopic and non-atopic subjects correlates fairly well with the total serum IgE levels (R2 = 0.817). BanLec also induces release of histamine (26.7%) from mast cells present in rat peritoneal exudate cells. BanLec can significantly activate and degranulate mast cells and basophils by cross-linking the trimannosidic core mannose of IgE glycans in atopic population as compared to non-atopic population; the activation is marginal in the case of non-atopics.